Analisis Tingkat Kesejahteraan Petani Karet di Desa Bangun Rejo Kecamatan Sukakarya Kabupaten Musi Rawas - Siti Alfiaturrohmah; Edy Suandi Hamid (INDO PUBLISHING, 2026)
This study aims to analyze the factors influencing the welfare of rubber farmers in Bangun Rejo Village, Sukakarya District, Musi Rawas Regency, including income, education level, work experience, land area, and production volume. This study employed a descriptive approach by combining quantitative and qualitative methods through ordinal logistic regression analysis based on primary data collected from 144 rubber farmers selected using purposive sampling techniques. The results showed that education level, work experience, land area, and production volume had a positive and significant effect on farmers’ welfare, while income had no significant effect. Land area was identified as the most dominant factor in improving farmers’ welfare, which was further strengthened by education level, work experience, and production volume. These findings indicate the importance of optimizing land management, increasing production capacity, and strengthening farmers’ skills through agricultural training and extension programs. This study contributes to the empirical literature on rural welfare by providing village-level evidence through the use of ordinal logistic regression in analyzing the determinants of rubber farmers’ welfare from a multidimensional socio-economic perspective in Musi Rawas Regency.